Access to medicines for rare diseases: beating the drum for primary ciliary dyskinesia. Issue 3 (14th September 2020) - Crowley, Suzanne; Azevedo, Inês; Boon, Mieke; Bush, Andrew; Eber, Ernst; Haarman, Eric; Karadag, Bulent; Kötz, Karsten; Leigh, Margaret; Moreno-Galdó, Antonio; Mussaffi, Huda; Nielsen, Kim G.; et al.
Rare diseases are collectively common, affecting an estimated 6.2% of the world's population [1], but each rare disease affects fewer than 4 to 5 in 10 000 individuals in Europe or less than 200 000 individuals in the USA [2]. Patients with rare diseases are often disadvantaged by late diagnosis and off-label prescribing of medicines [3]. Primary ciliary dyskinesia (PCD) is a genetic disease of impaired motile ciliary function that does not have a unique International Classification of Diseases (ICD)-10 code or licensed treatments, although Q34.8 denoting "other specified malformations of the respiratory tract" including nasopharyngeal atresia has also been applicable to PCD since 2017. The disease is characterised by mucus stagnation leading to chronic airway infection, bronchiectasis, chronic rhinosinusitis, reduced fertility and abnormalities of organ laterality with an associated increased risk of complex congenital heart disease [4]. The estimated prevalence of PCD in Europe is around 1 in 10 000 to 1 in 20 000 [5]. The international PCD cohort (iPCD) includes over 3800 PCD patients ranging in age from under 12 months to over 80 years, from Europe, Northern and Southern America, Australia and Western Asia [6]. Under-diagnosis of PCD is due to a lack of awareness among the general public and physicians in general, as well as a lack of diagnostic expertise in some countries [7]. Tools to help physicians identify patients needing testing ( e.g. PICADAR) [8] and the European Respiratory Society (ERS) guidelines for diagnostic testing [9] aim to improve this. In contrast to cystic fibrosis (CF), a monogenic disease, PCD is caused by mutations in one of at least 45 identified genes for which there is no effective mutation-specific therapy; this is likely to be a long way off for most patients [10]. Thus, treatment aims to prevent and manage disease complications. Even then, the lack of an evidence base for supportive treatment in PCD means that treatment recommendations are based on expert opinion and extrapolated from CF despite differing pathophysiology [11]. Primary ciliary dyskinesia, a rare disease causing bronchiectasis, lacks a sound evidence base for treatment. @beatpcd proposes 1) forming a PCD European clinical trial network to address this situation and 2) conducting n-of-1 trials to access medication. https://bit.ly/3j5blfM